ANALISIS KADAR TIMBAL (Pb) DAN MERKURI (Hg) PADA IKAN PINDANG SALEM (Scomber australasicus) YANG DIPEROLEH DARI TIGA PASAR TRADISIONAL TERBESAR DI KOTA SEMARANG - Aqnes Budiarti; Listyowati Listyowati; Henna Rya Soenoko (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2010)
ABSTRACT Smoked fish of Salem (Scomber australasicus) is kind of processing fish that well known in Indonesia. This study aim to detect presence of plumbum (Pb) and mercury (Hg) on smoked fish of Salem from traditional markets in Semarang. After determined its concentration, plumbum and mercury concentration in smoked fish of Salem were evaluated what were reached permissible limits based on standard of General Director Food and Drug Monitoring No. 03725/B/SK/VII/1989. This study is non-experimental research that analysed by analitycal descriptive method. Sample have been taken by simple random sampling from 9 sellers at three traditional markets in Semarang City that are Johar, Peterongan and Karangayu markets. Variabel which analysed were plumbum and mercury concentrations in smoked fish of Salem. Data were collected by laboratory test with Atomic Absorption Spectrophotometer. The results showed that smoked fish of Salem from three biggest traditional market in Semarang contained plumbum and mercury. Plumbum concentration on smoked fish of Salem from Johar market is 0.0633 ± 0.00577 mg/kg, from Peterongan market is 0.0600 mg/kg, and from Karangayu market is 0.0633 ± 0.00577 mg/kg. While mercury concentration on smoked fish of Salem from the three market are <0.01 mg/kg. Plumbum and mercury concentration on smoked fish of Salem from Johar, Peterongan, and Karangayu markets are not significant different. Plumbum and mercury concentration that accumulated on smoked fish of Salem from the three markets are not greater than quality standard of General Director of Food and Drug Monitoring No. 03725/B/SK/VII1989 about maximum restriction of metal pollution in food for fish and it processing result. Key words: smoked fish of Salem, determination, plumbum, mercury